2013
DOI: 10.4236/ojpsych.2013.31a010
|View full text |Cite
|
Sign up to set email alerts
|

Mood assessment via animated characters: An instrument to access and evaluate emotions in young children

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…These results echo previous efforts at digitizing measures for children and including pictorial representations such as the Dominic-R ( Valla et al, 2000 ) and MAAC ( Manassis et al, 2013 ) which demonstrated that children showed favorable opinions of digital assessments that incorporated visual images. However, these instruments tended to utilize only static images and characters to deliver assessment items and still relied on written words or a professional to read assessment questions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results echo previous efforts at digitizing measures for children and including pictorial representations such as the Dominic-R ( Valla et al, 2000 ) and MAAC ( Manassis et al, 2013 ) which demonstrated that children showed favorable opinions of digital assessments that incorporated visual images. However, these instruments tended to utilize only static images and characters to deliver assessment items and still relied on written words or a professional to read assessment questions.…”
Section: Discussionsupporting
confidence: 85%
“…Initial studies variously reported high user satisfaction and some clinical utility (i.e., computerized SDQ), moderate convergent validity (i.e., DI), and discrimination between anxious and nonanxious children (i.e., MAAC). Notably, all demonstrated improved engagement compared to standard pencil-and-paper versions suggesting visual, digital formats are favored by children ( Bergeron et al, 2013 ; Linares Scott et al, 2006 ; Manassis et al, 2013 ; Truman et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Screening directly with children may facilitate quick identification of a range of social and behavioral indicators [ 9 ], while also having the potential to capture internalizing (emotional) difficulties that parents or caregivers have not been able to observe [ 12 ]. However, there are numerous administrative challenges that may preclude children from responding or impact the reliability of the information collected [ 13 , 14 ]. Children may find the traditional text-based rating scales difficult because of their limited attention spans or difficulties with reading, language, and item comprehension [ 13 , 14 ], with these issues more pronounced in younger children (eg, 5-8 years).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are numerous administrative challenges that may preclude children from responding or impact the reliability of the information collected [ 13 , 14 ]. Children may find the traditional text-based rating scales difficult because of their limited attention spans or difficulties with reading, language, and item comprehension [ 13 , 14 ], with these issues more pronounced in younger children (eg, 5-8 years). In addition, given there are significant developmental variations between the ages of 5 and 12 years, crafting items using appropriate language that is broadly suitable across various ages is a challenge for scale developers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation